LOW CODE SOLUTIONS FOR MANAGING THE INTEGRATION OF VIDEO, GRAPHICS AND ACTIVE LEARNING RESOURCES FOR ENGAGING CLASSROOMS - Frank, Ian (PUPIL: International Journal of Teaching, Education and Learning, 2024)
Modern educators have access to ever-growing options for the creation of learning resources to foster engagement and comprehension. This paper describes an implemented low-code platform tailored to the needs of managing resource deployment and development. The metaphor of horizontal and vertical “slicing” is adopted from the field of software development to motivate the use of interfaces for managing diverse content, including video, banner graphics for delivering “Q&A” responses to student feedback, and a database of classroom activities. The effective marshalling of resources can help with enhancing interactivity and responsiveness in classrooms, and efficacy of the system is discussed through evaluation results showing that classes delivered via the system are at the very top of university-wide evaluation criteria